PENERAPAN METODE DRILL UNTUK MENINGKATKAN PRESTASI BELAJAR DALAM MENGHAFAL SURAT-SURAT PENDEK DALAM AL-QUR’AN - SITI SUPIYATUN (TEACHER : Jurnal Inovasi Karya Ilmiah Guru, 2022)
This study aims to improve student achievement in memorizing short surahs in the Qur'an by applying the drill method. This research is a classroom action research. Data collection techniques are observation, interviews, questionnaires, and tests. The research procedure consists of five stages, namely planning, preparation, implementation, data processing, and preparing reports. Research instruments include learning implementation plans (RPP), questionnaires or questionnaires, assessment formats and lists of students, performance tests. 8. Data analysis techniques use descriptive qualitative analysis techniques and percentage descriptive data analysis techniques. Research results for the first cycle of students were given a pretest with the results of 25 students who achieved completeness were 8 students with an average test score of 65.6, 32% of students who passed. 2. In cycle II, the test results of 25 students were 15 students who passed with an average score of 77.5, 69% of students who passed. 3. In cycle III the test results of 25 students there were 25 students who passed with an average score of 97.2, students who completed reached 100%. To carry out effective learning requires sufficient preparation, so the teacher must be able to determine or choose topics that can really be applied with the drill method. ABSTRAKPenelitian ini bertujuan untuk meningkatkan prestasi belajar siswa dalam menghafal surat-surat pendek dalam Al-Qur’an dengan penerapan metode drill. Penelitian ini merupakan penelitian tindakan kelas. Tehnik pengumpulan data adalah observasi, wawancara, kuesioner, dan tes. Prosedur penelitian ada lima tahap yaitu perencanaan, persiapan, pelaksanaan, pengolahan data, dan penyusuan laporan. Instrumen penelitian meliputi Rencana Pelaksanaan Pembelajaran (RPP), Angket atau kuesioner, Format penilaian dan daftar siswa, tes unjuk kerja. 8. Tehnik analisa data menggunakan tehnik analisa deskriptif kualitatif dan tehnik analisa data deskriptif prosentase. Hasil Penelitian untuk siklus I siswa diberi pretest dengan hasil dari 25 siswa yang mencapai ketuntasan adalah 8 siswa dengan nilai rata-rata tes 65,6, siswa yang tuntas adalah 32%. 2. Pada siklus II hasil tes dari 25 siswa ada 15 siswa yang tuntas dengan nilai rata-rata 77,5, siswa yang tuntas adalah 69%. 3. Pada siklus III hasil tes dari 25 siswa ada 25 siswa yang tuntas dengan nilai rata-rata 97,2, siswa yang tuntas mencapai 100%. Untuk melaksanakan pembelajaran yang efektif memerlukan persiapan yang cukup, sehingga guru harus mampu menentukan atau memilih topik yang benar-benar bisa diterapkan dengan metode drill.